Applications of surface vibrational spectroscopic techniques - Hargreaves, Elaine Carol (1997)
An advanced Electron Energy Loss Spectrometer has been used to study the formation of 3,3,3-trifluoropropylidyne on Pt (111). This has been compared to the results from the same system using the complementary vibrational spectroscopic technique of Reflection Absorption Infrared Spectroscopy (RAIRS). This study demonstrates the improved resolution of the new spectrometer. The thermal decomposition products, CF3 and CF2 have been detected in the Electron Energy Loss (EEL) spectra.